ANALYSIS OF CONSUMER INTEREST THROUGH THE ZALORA E-COMMERCE APPLICATION - Wahyuni, Tri Indah; Fahrudin, Fahrudin; Masruroh, Nuril; Rachmawati, Rica; Jannah, Lailatul; Firdausi, Jinnani; Lestari, Eka Dwi; Muthi’ah, Nadia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Technological developments from time to time are increasingly sophisticated in line with people's lifestyles which are now switching to using artificial devices to make it easier to meet their needs. This includes completing secondary needs such as clothing and beauty products which can be reached through e-commerce applications. An e-commerce application is an application that provides online buying and selling services with supporting features that facilitate human mobility to meet needs. Among several e-commerce sites that are spread and developing in Indonesia, one of the most trusted and popular e-commerce applications that offers high-quality fashion products is the Zalora application. The quality of different products causes price variations. This variation in prices offered then becomes one of the factors that influences consumer interest in the Zalora e-commerce application. Therefore, this research was conducted to find out how much influence the existence of the Zalora e-commerce application has on consumer interest. In this scientific work, we used quantitative research methods in the form of questionnaires submitted to several participants from various backgrounds and ages to find the conclusion that consumer interest in the Zalora e-commerce application is influenced by several factors that significantly influence purchasing decisions in e-commerce applications. Zalora. These factors include: product quality, price variations offered, frequency of discount offers, ease of delivery, and ease of making payments.